The effects of knowledge transfer on farmers decision making toward sustainable agriculture practices: In view of green fertilizer technology. Issue 1 (2nd January 2018) - Adnan, Nadia; Nordin, Shahrina Md; Rahman, Imran; Noor, Amir
Abstract : Purpose: The purpose of this paper is to enhance the adoption decision of farmers and observe the factors that affect the adoption decision of sustainable agriculture practices (SAP) which is the major motivating force of Malaysian economy. The idea behind this study is to transfer knowledge to paddy farmers within regional areas of Malaysia and to comprehend their understanding of social innovation and sustainable agriculture engineering and their overall significance. The outcome of this research will suggest a strategic extensive plan to encourage the use of SAP and also help to develop SAP helping toward building a sustainable society. Design/methodology/approach: This paper encompasses three phases: analyzing the process of SAP among Malaysian Paddy farmers, to agricultural industrialization, until the stage of SAP led by farmer's co-operatives, discussing the relevant practice together with literature and historically evidencing that there is no better way to promote SAP among regional paddy farmers within Malaysia. Findings: Initial objective of this paper is to establish a thoughtful approach to enable the society to bridge a gap between embracing sustainability. The second objective investigates the misconception among farmers about social innovation. Furthermore, the study builds the conceptual framework and examines the relationship among the relevant constructs, this framework is critically examining the literature within paddy farming context. Harmoniously, there has been limited empirical research performed on the decision of adoption toward SAP usage among paddy farmers in Malaysia. Originality/value: The clear worth of this research paper is the illustration from past reviews and practices to endorse SAP usage among paddy farmers in Malaysia. Another literature review suggests that these countermeasures comprehensively, historically, and theoretically are proven result oriented. The information about SAP will be beneficial for farmers and policy maker who are interested in the advancement. This learning delivers a comparative summary of knowledge transfer influencing farmer's intention and behavior of sustainable agriculture engineering to adopt green technology. In a future study, these construct will be empirically tested.